POLA DAN BENTUK KOMUNIKASI KELUARGA DALAM PENERAPAN FUNGSI SOSIALISASI PERKEMBANGAN ANAK DI PERMUKIMAN DAN PERKAMPUNGAN KOTA BEKASI - Afrina Sari (Fakultas Komunikasi, Sastra, dan Bahasa, 2011)
This research purpose that the family communications pattern analysis, function of socialization of family, form of communication happened at family who live in setlement and countrified in Bekasi City. Besides, also to know development of child of the the family. Method which in using in this research is descriptive method uses descriptive survey design, data analysis Statistik by using anova, wilcoxon and Rank Spearmen analysis. Result of research indicates that communications pattern to family in setlement is more usingly is combination pattern between patterns laisez-faire, protektif, pluralistic, and konsensual. Its use in corresponding to various conditions and situation when mothering. Function of active socialization, passive and radical in using in combination by family who live in setlement and countrified. In mother tongue usage ( area), both types of the family applies for inuring and recognition to child of child of they.